Urgensi Penerapan Manajemen Pendidikan Islam Di Era Global - Mohammad Adnan (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2019)
Abstract: Globalization is an inevitable necessity for those who expect progress. The presence of globalization demands a fundamental change for every individual to see the flow of globalization as a necessity, not as a threat. In responding to the challenges of globalization, human resources with high character and high competitiveness are needed. To make it happen, this is where Islamic education must present itself as part of the challenge of globalization. Education is the key for a nation to maintain its existence where increasing skills and abilities are believed to be a factor in preparing for a future that is ready to compete with other nations. students through Islamic teachings towards the maximum point of growth and development. Thus, the essence of management of Islamic education is the management of various activities carried out by adults consciously in directing and guiding the growth and development of students towards the maximum point (Muslim personal) effectively and efficiently. That is, management of Islamic education in the era of globalization as it is today, must still be able to guide humans to remain human beings who have high human values ​​that are in line with the teachings contained in the Qur'an and the hadith of the Prophet Muhammad. So that education in the context of the globalization era such as the value of education will never lose its direction and purpose, this can be done when the management of Islamic education can really be applied properly and in accordance with the laws and provisions of the Islamic religion.